End of Meeting Report - ISPC 13 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2016)
The thirteenth meeting of the ISPC was held from the 25-27 May 2016 at CIP Headquarters, Lima, Peru. View presentations here (https://www.slideshare.net/ISPC-CGIAR/tag/ISPC13)